Analysis results of biological water quality parameters in lake Naplás - Schumacher, Fanni; Waltner, István; Sebők, András; Grósz, János (JOURNAL OF LANDSCAPE ECOLOGY, 2022)
Qualitative and quantitative protection of surface water is one of the highlighted tasks because it is the most decisive natural resource. Water quality measurements contain biological, chemical, physical and bacteriological parameters. The main purpose of the study to determine which parameters affect the horizontal and vertical distribution of phytoplankton. The study area is the Lake Naplás which is the second largest nature reserve of Budapest. During the sampling campaigns, chlorophyll-a, NO2-, NO3-, PO43- concentration, water temperature, UV index and meteorological parameters were measured. Based on the results, the vertical and horizontal location of the phytoplankton was mostly influenced by UV radiation, water temperature, NO3- and the PO43- content.